The Alcohol Intervention Training Program (AITP): A response to alcohol misuse in the farming community - Ricciardelli Lina A; McCabe Marita P; Mellor David; Kennedy Alison J; Brumby Susan A; Head Alexandra; Mercer-Grant Catherine (BMC, 2011)
Abstract Background Farm men and women in Australia have higher levels of problematic alcohol use than their urban counterparts and experience elevated health risks associated with excessive alcohol consumption. The Sustainable Farm Families (SFF) program has worked successfully with farm men and women to address health, well- being and safety and has identified that further research and training is required to understand and address alcohol misuse behaviours. This project will add an innovative component to the program by training health professionals working with farm men and women to discuss and respond to alcohol-related physical and mental health problems. Methods/Design A mixed method design with multi-level evaluation will be implemented following the development and delivery of a training program (The Alcohol Intervention Training Program AITP) for Sustainable Farm Families health professionals. Pre-, post- and follow-up surveys will be used to assess both the impact of the training on the knowledge, confidence and skills of the health professionals to work with alcohol misuse and associated problems, and the impact of the training on the attitudes, behaviour and mental health of farm men and women who participate in the SFF project. Evaluations will take a range of forms including self-rated outcome measures and interviews. Discussion The success of this project will enhance the health and well-being of a critical population, the farm men and women of Australia, by producing an evidence-based strategy to assist them to adopt more positive alcohol-related behaviours that will lead to better physical and mental health.